2007
DOI: 10.4028/www.scientific.net/kem.330-332.1263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grinding, Sandblasting and Heat Treatment on the Phase Transformation of Zirconia Surface

Abstract: This study was aimed to investigate the effect of grinding, sandblasting by alumina and SiC, and heat treatment on the phase transformation from tetragonal to monoclinic zirconia on the surface of yttria stabilized tetragonal zirconia (Y-TZP) and zirconia/alumina nanocomposite stabilized with cerium oxide (Ce-TZP/Al2O3 nanocomposite). The monoclinic phase content of both materials increased with the grinding and the sandblasting, while it decreased with the heat treatment. The monoclinic content sequentially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The irreversible tetragonal-to-monoclinic transformation of zirconia, caused DENTAL-2458; No. of Pages 11 d e n t a l m a t e r i a l s x x x ( 2 0 1 4 ) xxx.e1-xxx.e11 xxx.e9 by low temperature degradation property or different surface treatments such as sandblasting or acid etching, leads to an increase in the surface's monoclinic content [26,[34][35][36]. This increase has been shown to cause stress fields that lead to the development of defects, including surface and subsurface micro-cracking, grain pull-out and damage of the material's surface [26,69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The irreversible tetragonal-to-monoclinic transformation of zirconia, caused DENTAL-2458; No. of Pages 11 d e n t a l m a t e r i a l s x x x ( 2 0 1 4 ) xxx.e1-xxx.e11 xxx.e9 by low temperature degradation property or different surface treatments such as sandblasting or acid etching, leads to an increase in the surface's monoclinic content [26,[34][35][36]. This increase has been shown to cause stress fields that lead to the development of defects, including surface and subsurface micro-cracking, grain pull-out and damage of the material's surface [26,69].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low temperature degradation (LTD), also termed "aging", of the meta-stable tetragonal phase to monoclinic zirconia with time is considered a serious limitation of this material [14,34]. Also surface-roughening procedures that are used for titanium may influence zirconia surface properties negatively [35,36]. Thus, there is a need for specific surface modification techniques to enhance the clinical outcomes compared with current problems associated with "conventional" zirconia surface roughening procedures [37].…”
Section: Introductionmentioning
confidence: 99%
“…The strength of Y-TZP decreases with sandblasting, and it has been reported that biaxial flexural strength decreases by 10% 28,29) . Sandblasting induces the phase transformation of TZP, which causes a decrease in strength.…”
Section: Influence Of Heat Treatmentmentioning
confidence: 99%
“…However, not all crystals undergo phase transformation to tetragonal zirconia, and 0.6% of the zirconia remains as monoclinic zirconia 28,29) . In the present study, the ratio of monoclinic phase after both sand blasting and heat treatment was 0.6±0.2%.…”
Section: Influence Of Linermentioning
confidence: 99%
“…It can be explained that the transformation from tetragonal to monoclinic by sandblasting expands their volume to generate compressive stress on the surface, resulting in increasing of strength and the regeneration of tetragonal phase by annealing reduces the compressive stress on the surface, resulting in decreasing of strength. We compared the effects of these treatments of NANOZR to Y-TZP [36][37][38][39][40][41]. [ Core material for all-ceramic dental restorations…”
Section: Effect Of Sandblasting and Heat Treatmentmentioning
confidence: 99%